Władza i odpowiedzialność przedsiębiorstw w obliczu konfliktu ekologicznego : Wstępne wyniki analiz empirycznych - Strumińska-Kutra, Marta (Power and Responsibility of Enterprises in the Face of Ecological Conflict : Initial Results of Empirical Analyses, 2009)
Corporate Social Responsibility is analyzed form the institutional perspective. It assumes that the question of companies' actions cannot fully be answered without examining its broadly understood social environment. Institutional approach is completed here by the theory of resources dependency. These two perspectives encompass different kinds of determinants, accordingly: values, norms, and social expectations towards business organization and interconnections between business organization and its stakeholders. These interconnections function as channels for resources transfer (capital, labour, commodities, information, knowledge and last but not least legitimization) and create certain power relations. The implementation of CSR in Poland confronts as well specific social environment as specific power relations. One of the ways to capture these pieces of specific influence is to examine conflict between a company and its external stakeholders. It allows to observe norms and values driving actors behaviour - not only on the declarations level, but also on the level of (forced) actions. It allows to capture significant influence of companies' environment consisting of different collective and individual actors and institutions. This paper introduces initial results of empirical examination based on case study research.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 211-224